2019
DOI: 10.1186/s12866-019-1604-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root exudates of Eucalyptus urophylla and Acacia mearnsii on soil microbes under simulated warming climate conditions

Abstract: Background Recent studies demonstrated that warming and elevated carbon dioxide (CO2) indirectly affect the soil microbial community structure via plant root exudates. However, there is no direct evidence for how the root exudates affect soil microbes and how the compositions of root exudates respond to climate change. Results The results showed that warming directly decreased biomass of soil-borne bacteria and fungi for Acacia mearn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The positive response of Rs to soil temperature change may be related to the variations of soil matrix availability and microbial abundance (Noh et al 2017;Sun et al 2019). Previous studies have shown that warming may increase FRB, root exudates or litter decomposition (Gong et al 2015;Liu et al 2017b;Wu and Yu 2019). In our study, FRB in July was signi cantly higher than that in May (Fig.…”
Section: Effects Of N Addition On Rssupporting
confidence: 51%
“…The positive response of Rs to soil temperature change may be related to the variations of soil matrix availability and microbial abundance (Noh et al 2017;Sun et al 2019). Previous studies have shown that warming may increase FRB, root exudates or litter decomposition (Gong et al 2015;Liu et al 2017b;Wu and Yu 2019). In our study, FRB in July was signi cantly higher than that in May (Fig.…”
Section: Effects Of N Addition On Rssupporting
confidence: 51%
“…Tree species (host) can select the soil microbiota, for instance, by the effects of tree species identity (Wubet et al ., 2009; Weißbecker et al ., 2018) and the genotype (KarliƄski et al ., 2020). These effects can be mediated through modulating the soil chemistry resources (UrbanovĂĄ et al ., 2015; Wu and Yu, 2019). Assuming that each tree species to some extent can have species‐specific and generalist soil microbial communities, one would expect an increasing number of microbial species with increasing tree diversity covering more and more taxa of the local microbial species pool.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of A. mearnsii to adapt rapidly to future climate change implies that it can easily overcome invasion barriers and constraints caused by climate change, thus, becoming more invasive in future [ 42 ]. For example, Wu and Yu [ 45 ] showed that although soil microorganisms underneath A. mearnsii soils are sensitive to increased warming and elevated CO 2 , A. mearnsii tends to respond by increasing root exudates and root length, which subsequently increases its growth through increased nutrient uptake and photosynthetic capacity. Based on the above-mentioned study, the positive effect of increased warming and elevated CO 2 on A. mearnsii root exudates and root length can be viewed as an environmental adaptation strategy.…”
Section: Discussionmentioning
confidence: 99%